Mechanics of structure genome-based buckling analysis of sandwich structures. (December 2021) - Liu, Ning; Yu, Wenbin
Abstract: Sandwich structures are important structural members in modern lightweight engineering. Accurate and effective buckling predictions are vital to the design and optimization of sandwich structures. This paper extends and validates a homogenization theory namely the mechanics of structure genome (MSG) in predicting eigenvalue buckling of sandwich structures under compressive and bending loads. Global buckling is predicted on a homogeneous plate with effective plate properties computed by MSG. Local buckling is predicted by perturbing the fluctuating function of structure gene under Bloch-periodic boundary conditions. Accuracy of buckling predictions is validated by three-dimensional finite element analysis. Highlights: Mechanics of structure genome for global and local buckling of sandwich structures. Buckling of sandwich structures under both compressive load and bending load. Bloch-periodic boundary conditions used in mechanics of structure genome models. New buckling modes including type II flexural modes and torsional modes identified.